2020
DOI: 10.1155/2020/5391379
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Isolation, Chemical Properties, and Bioactivities of Polysaccharides from Bletilla striata

Abstract: Recently, polysaccharides from Bletilla striata, a member of the orchidaceous family, aroused the wide interest of people, especially their isolation, chemical properties, and bioactivities. It is reported that these polysaccharides are the most important biologically active components of B. striata, exhibiting various biological activities, such as immunomodulatory, antioxidant, antifibrotic, and hemostatic effects. This review appraised the available literatures which described different aspects of B. striat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…After concentration, the purified BSPs were obtained from eluent. [2] Finally, purified BSPs have been widely studied in many aspects (Figure 1).…”
Section: Separation and Purification Of Bspsmentioning
confidence: 99%
See 2 more Smart Citations
“…After concentration, the purified BSPs were obtained from eluent. [2] Finally, purified BSPs have been widely studied in many aspects (Figure 1).…”
Section: Separation and Purification Of Bspsmentioning
confidence: 99%
“…BSPs had significant antitumor activities in vivo and in vitro. [2] Li et al [53] found that previously investigated the in vivo and in vitro effects of paclitaxel nanoparticle-(PTX-) loaded BSPs on human gastric cancer cells. The results suggested that BSP-loaded paclitaxel nanoparticles could realize enhanced drug delivery and exert an antiproliferative effect on the human gastric gland cancer cell line (MKN45) effectively and safely both in vivo and in vitro.…”
Section: Other Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in China, the dried tubers of B. striata , recorded as “Bai ji” in Chinese pharmacopoeia (2010), has been used as a traditional Chinese medicine (TCM) for thousands of years. In the modern times, many beneficial health effects of B. striata , such as healing, hemostasis, antioxidation, antiinflammation, antifibrotic and immunomodulatory activities, have been uncovered by the recent phytochemical and pharmacological studies [ 2 , 3 ]. Recently, China Food and Drug Administration has approved four patent medicines including “Bai ji” Pill, “Bai ji” Capsule, “Bai ji” Syrup, and “Bai ji” Granule, all of which contain B. striata as the unique medicinal ingredient [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides have attained limelight due to their various biologic properties, nontoxicity and biodegradable nature [ 21 ]. BSP is known to possess anti-inflammatory, antioxidant and antiviral properties [ 22 , 23 ]. Previous study showed that polysaccharides from Bletilla striata can successfully alleviate ROS generation and proinflammatory cytokines activation induced by Angiotensin II in human mesangial cells (HMCs), exhibiting antioxidant and anti-inflammatory properties of BSP [ 24 ].…”
Section: Introductionmentioning
confidence: 99%